Impact of health capital on total factor productivity in Singapore - Isreal, Akingba Idowu Opeoluwa (Universiti Kebangsaan Malaysia, 2019)
The significance of health capital as a major determinant of economic growth and productivity was highlighted through the work by Jeremy Bentham (1780). In subsequent era, economists likewise acknowledged that individual and population health could be one of the important determinant of productivity and economic growth. This paper examines the impact of health capital on multi-factor productivity (hence TFP) in Singapore covering the period of 1980-2013. The finding from the Autoregressive Distributed Lag (ARDL) bound test shows that there is stable and long run co -integration between TFP, health capital, and education. The long run estimate shows that health capital and education makes a positive and substantial contribution to TFP. This indicates that the TFP of Singapore could be substantially improved if spending on health capital and education are increased accordingly